Group Classification and Solutions of a Mathematical Model from Tumour Biology - Ibragimov, N.H.; Tracina, R.; Avdonina, E.D. (Discontinuity, Nonlinearity, and Complexity, 2026)
We are interested in symmetries of a mathematical model of a malignant tumour dynamics due to haptotaxis. The model is formulated as a system of two nonlinear partial differential equations with two independent variables and contains two unknown functions of the dependent variables. When the unknown functions are arbitrary, the model has only two symmetries. These symmetries allow to investigate only travelling wave solutions. The aim of the present paper is to make the group classification of the mathematical model under consideration and find the cases when the model has additional symmetries and hence additional group invariant solutions.